PENGARUH PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK TERHADAP MINAT DAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SEKOLAH DASAR PADA MATERI PECAHAN - E'en, E'en; Hartoyo, Agung; Zubaidah, Zubaidah; Djudin, Tomo; Suratman, Dede (Universitas Tanjungpura, 2026)
This study aims to determine the influence of the realistic mathematics education (PMR) approach on the learning interest and critical thinking ability of grade IV students in fractional materials. The study used a quantitative method with a posttest-only control group design. The sample amounted to 43 students who were divided into experimental classes with PMR learning and control classes with conventional learning. The research instruments include a learning interest questionnaire and a validated critical thinking ability test. The results showed significant differences between the two classes. The learning interest of students in the experimental class was higher than that of the control class (p < 0.05). The critical thinking skills of students in the experimental class were also significantly improved (p < 0.001). These findings prove that PMR is effective in increasing interest and high-level thinking skills. Research recommends the implementation of PMR as a learning strategy in primary schools.